The influence of professional sport on changes in the athlete`s cardiovascular system after the end of career - Nikolic, T.; Zbucnovic, S.; Ujsasi, D.; Milic, Z. (Sports Science and Health, 2021)
The benefits of sports activities on almost all are immense and of wide spectrum. However, a large number of recent studies deals with the consequences of long-term professional engagement in sports activities and present opposite results. The review was based on the assumption that intense physical activity to which top athletes are exposed brings with it changes in the cardiovascular system. The methodological procedure has included a review of previous research through the Google Scholar, PubMed, Scopus and Web of Science search engines over the past twenty years. Athletes who have played endurance sports have lower blood pressure values compared to athletes who have played strength sports, as well as compared to the non-athlete population. Athletes who have been involved in strength sports have more pronounced left ventricular values. As a general conclusion, it can be pointed out that intense physical activity contributes to changes in the cardiovascular system, but further monitoring of the athlete`s condition is needed after a professional career, in order to obtain even clearer results, because sport is performed at an extremely intensive level, higher than 50-60 years ago.